DINAMIKA KETAHANAN PANGAN KELUARGA PETANI PADI SAWAH (STUDI: KELUARGA PETANI PENGGARAP DI KECAMATAN WARA, KOTA PALOPO) - NADILA, NADILA (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2026)
Rice farmers' families' food security is crucial, particularly in urban-rural transition zones like Wara District Palopo City. The Household Food Insecurity Access Scale (HFIAS) will be used to investigate rice farming households' food security dynamics and economic feasibility. This census included all 50 rice farming households in Wara District, Palopo City. Data was acquired via structured questionnaires on demographics, land access, agricultural systems, household spending, and food security. The Benefit-Cost (B/C) and Income-Cost (R/C) ratios determine the economic viability of alternative planting methods, whereas the HFIAS classifies families as food secure, mild, moderate, or severe. Most responders (41-60 years old) are productive and have secondary education. Family sizes average 4-5 and land ownership is 0.25-1 Ha. With an average HFIAS score of 7.04, families have minor food insecurity. Rice availability is consistent, but dietary diversification, notably vegetable and fruit intake, is restricted. The Legowo 2:1 approach yields the maximum net revenue and efficiency in agricultural systems, although the Tabela method is more popular owing to its simplicity. Finally, rice farmers in Wara District, Palopo City enjoy the most basic food security but are subject to food shortages and economic shocks. Household food security requires policy assistance, notably in land conservation, income diversification, and nutrition education.